2008
DOI: 10.1037/0022-006x.76.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Primary Care Posttraumatic Stress Disorder Screen and the Posttraumatic Stress Disorder Checklist with soldiers returning from combat.

Abstract: The purpose of the research was to assess the diagnostic efficiency of the Primary Care Posttraumatic Stress Disorder Screen (PC-PTSD) and the Posttraumatic Stress Disorder Checklist (PCL) as clinical screening tools for active duty soldiers recently returned from a combat deployment. A secondary goal was to examine the item-level characteristics of both the PC-PTSD and the PCL. A validation study conducted with a sample of 352 service members showed that both the PC-PTSD and PCL had good diagnostic efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
571
3
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 697 publications
(594 citation statements)
references
References 38 publications
15
571
3
3
Order By: Relevance
“…Cronbach’s alpha was 0.91. PTS was measured by PCL-6, a short version (Lang & Stein, 2005) of the PTSD Check List (PCL for DSM IV) (Bliese et al, 2008). Cronbach’s alpha was 0.84.…”
Section: Methodsmentioning
confidence: 99%
“…Cronbach’s alpha was 0.91. PTS was measured by PCL-6, a short version (Lang & Stein, 2005) of the PTSD Check List (PCL for DSM IV) (Bliese et al, 2008). Cronbach’s alpha was 0.84.…”
Section: Methodsmentioning
confidence: 99%
“…Suggested cut‐point scores ≥30 have the best sensitivity and specificity for screening active‐duty military service members for traumatic stress (Bliese et al. 2008). …”
Section: Methodsmentioning
confidence: 99%
“…2,[11][12][13] Further, Freedy and his colleagues found that the PC-PTSD performed similarly to the PTSD Checklist -Civilian version (PCL-C) 2 , a wellestablished longer measure of PTSD that assesses the full range of symptoms. 14,15 Because the PC-PTSD has demonstrated excellent diagnostic accuracy and clinical utility with various groups of primary care patients, 2,9,16,17 it is mandated for use in VA and DoD settings. 18,19 In 2013, the fifth edition of the Diagnostic and Statistical Manual (DSM-5) 20 introduced significant revisions to the PTSD diagnosis based on research suggesting that these changes better reflect the PTSD latent construct.…”
Section: T He Prevalence Of Posttraumatic Stress Disorder (Ptsd) Inmentioning
confidence: 99%